Red clover and plant growth promoting bacteria: The combination that can speed up soil remediation rate - Karlicic, Vera M; Radic, Danka; Jovičić Petrović, Jelena; Raičević, Vera (Journal of Agricultural Sciences (Belgrade), 2020)
Abstract: Phytoremediation is widely accepted method for eco-friendly and cost-effective soil remediation. Plant remediation mechanisms are strongly supported by microorganisms inhabiting root zone. Rhizosphere microorganisms are employed through bioremediation process and they stimulate pollutants degradation and speed up remediation kinetics. The key factor for successful phyto/bioremediation is the adequate choice of plant species and bacterial strains. In this study, red clover (Trifolium pretense L.) was inoculated with several plant growth promoting bacteria and sown in the substrate contaminated with PAHs, PCBs and organotin substances. The aim was to determine if selected PGPB strains can promote growth of red clover in substrate contaminated with several organic pollutants. The influence of bacteria on red clover growth (height, root length and biomass) was monitored during tree mounts experimental period. The highest improvements of seedlings height were noted in treatment with Bacillus amyloliquefaciens D5 ARV and Pseudomonas putida P1 ARV. Root growth was positively affected by Serratia liquefaciens Z-I ARV. The same isolates significantly affected biomass production. Those isolates caused total biomass increase of 70%, 48% and 33% compared to control. Obtained results confirmed that inoculation with several PGPB strains promote red clover growth and have potential to improve red clover remediation potential